Agri-environmental policies in a transitional economy: the value of agricultural biodiversity in Hungarian home gardens - Birol, Ekin; Smale, Melinda; Gyovai, Agnes (International Food Policy Research Institute, 2004)
Agricultural biodiversity is an environmental resource. Much of the agricultural biodiversity remaining in situ today is found on the semi-subsistence farms of poorer countries and the small-scale farms or home gardens of more industrialized nations. The traditional small farms of Hungary are labelled “home gardens” as a reflection of their institutional identity during the collectivisation period. Homesteads managed with family labor, they continue to serve essential food security and diet quality functions during economic transition. Home gardens contribute to the preservation of rural settlements and cultural heritage, and they contain relatively high levels of several components of agricultural biodiversity. The role of home gardens in the agri-environmental program that is now being formulated by Hungary and the European Union has not been elucidated, though the stated goal of these policies is to support multifunctional agriculture. This study estimates the private value that Hungarian farmers assign to home gardens and their biodiversity attributes, and indicates how such information might be used in designing least-cost mechanisms to support their maintenance as part of the national agri-environmental program. -- Authors' Abstract